The Pendampingan Pengolahan Pare Bagi Kelompok Wanita Tani (KWT) Ngolang yang Terdampak Pembangunan KEK Mandalika: - - Yuli Rahmawati; Siska Ita Selvia; Nur Shapna Dwiyanti; Mukminah; Nur Asri Shakila (Universitas Mataram, 2023)
The purpose of this community service activity is to introduce and open up the knowledge of the Ngolang Women Farmer Group (KWT) community about the great potential and opportunities of the region, increase local food processing capabilities and increase institutional capacity. This activity was carried out in Ngolang Sub-Village, Kuta Village, Pujut District, Central Lombok Regency, involving 20 Ngolang KWT members. The method used in this community service is lectures and training in the form of direct practice of food processing. The raw material that is processed is bitter melon, as well as an effort to integrate bitter melon cultivation, which is also being cultivated in the surrounding villages. As a result of this community service activity, the community can have information disclosure about the potential of the area where they live as a buffer zone for the KEK Mandalika, which has excellent potential for UMKM development. Community enthusiasm can be seen from the high participation and confidence in these service activities.